Dental Tissue Repair: Novel Models for Tissue Regeneration Strategies - Sloan, Alastair J (Bentham Open, 2012)
Studies have shown that dentin matrices contain reservoirs of bioactive molecules capable of directing tissue repair. Elucidating the release mechanisms of such endogenous growth factors will enhance our understanding of dentinpulp regeneration and support the development of novel treatment modalities to enhance dentin repair following trauma and disease. Current clinical practice using new materials which are perceived to maintain pulpal viability require biological evidence to assess their therapeutic benefit and there is a need for better effective methods of assessing therapeutic approaches to improving dentin regeneration at the cellular and tissue level. Experimental modelling of dentin regeneration is hampered by the lack of suitable models. In vivo and in vitro studies have yielded considerable information on the processes taking place, but are limited, due to the cost, ethics and lack of cell/matrix interactions. Novel organotypic models, whereby cells and tissues are cultured in situ may provide a more suitable model system to facilitate dental tissue engineering and regeneration.